1978
DOI: 10.1007/bf01966611
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of synovial fluid lysosomal glycosidases by anti-Arthritic gold preparations

Abstract: The ability of currently available anti-arthritic gold preparations to inhibit lysosomal glycosidases from rheumatoid synovial fluid and normal human serum was studied in vitro.It was shown that these preparations differ markedly in their ability to inhibit the enzymes. Gold thioglucose (Solganal) did not inh~it ~-glucuronidase ~-GLUC), ~-Nacetylglucosaminldase (t-NAG) or hyaluronidasc (HASE). Chloro(triethylphosphine)gnld (SK&F 36914) was a potent inhibitor oft-NAG only. Sodium aurothlomalate (Myochrysine and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…As was confirmed in this study, gold thiomalate can inhibit fl-glucuronidase [24,[26][27][28][29]32] and acid phosphatase [26,31,32] in vitro. The concentrations required, however, are far in excess of those maintained in vivo in plasma either during chrysotherapy [52] or, similarly, during the weekly injection schedule of this study.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…As was confirmed in this study, gold thiomalate can inhibit fl-glucuronidase [24,[26][27][28][29]32] and acid phosphatase [26,31,32] in vitro. The concentrations required, however, are far in excess of those maintained in vivo in plasma either during chrysotherapy [52] or, similarly, during the weekly injection schedule of this study.…”
Section: Discussionsupporting
confidence: 69%
“…Direct addition of gold to isolated cells can cause an increase in F e receptor activity [171, inhibition of monocyte to macrophage differentiation [18], inhibition of accessory cell function in humoral and cellular immune mechanisms [19], reduction of monocyte chemotaxis [20], and diminished capacities for pinocytosis [21], phagocytosis [21][22][23], adherence [22] and digestion [18]. Further, gold has inhibitory effects on lysosomal enzymes [24][25][26][27][28][29][30][31][32] and prostaglandin formation [33] in vitro. However, the relevance of this information to the in vivo circumstance is uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Autometallographic (AMG) studies have revealed that gold ions originating from gold salts have their metabolic end station in the lysosomal compartment, and the excess accumulation of gold containing macromolecules causes rupture of the lysosomal membrane (Davies et al 1971, Burkhardt et al 1978Danscher 1981Danscher , 1991Brunk et al 1997;Møller-Madsen et al 1984). Gold ions resulting from gold salts have also been shown to be transported over the placental barrier and into the human embryo (Møller-Madsen et al 1987) and to accumulate in the dorsal root ganglia (Schiønning et al 1992).…”
mentioning
confidence: 97%
“…Gold salts decrease monocyte secretory and phagocytic capacity (23)(24)(25), impair monocyte chemotaxis and migration (26,27), and inhibit lymphocyte proliferation to antigens and mitogens (28,29). C1 and several lysosomal enzymes are inactivated by gold salts (30)(31)(32). These effects serve to down-regulate the exuberant inflammatory response characteristic of active RA.…”
mentioning
confidence: 99%